Fenomena Ikhtilāf di Kalangan Masyarakat Islam Kota Makassar; Studi Perbandingan antara Nahdlatul Ulama dan Wahdah Islamiyah - Nursain, Muhammad Rezky Ranuwijaya; Musyahid, Achmad (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
This article aims to uncover the phenomenon of ikhtilaf among the Islamic community of Makassar city which is devoted to the study of comparison between Nahdlatul Ulama and Wahdah Islamiyah). This type of field research uses a normative approach. The source of this research data is the primary data source namely the leadership of Nahdlatul Ulama and Wahdah Islamiyah Makassar city and secondary data source namely Qur'an, hadith, fiqh, books, journals, and literature related to the discussion of this article. The results of this study suggest that Nahdlatul Ulama and Wahdah Islamiyah Makassar city in applying the law using the legal resources agreed by jumhur Ulama, namely: Qur'an, As-Sunnah, ijma, and qiyas. Nahdlatul Ulama and Wahdah Islamiyah also use legal sources that are not agreed by jumhur Ulama such as istishan, mashlahah al-mursalah, and others but prefer the source of the law that has been agreed by jumhur Ulama. Nahdlatul Ulama and Wahdah Islamiyah Makassar city differ in terms of commemorating the maulid of the Prophet Muhammad. In this case, Nahdlatul Ulama commemorates the anniversary of maulid while Wahdah Islamiyah does not commemorate it. Nahdlatul Ulama and Wahdah Islamiyah Makassar city considers that the phenomenon of ikhtilaf will not be solved, but what can be solved is our way of addressing the ikhtilaf, and the attitude is mutual tolerance, mutual respect, mutual respect, and mutual support. The implication of this article is expected to be expected to the Islamic community when looking at the phenomenon of ikhtilaf, especially in terms of furu', should not be to concern each other. When the phenomenon of ikhtilaf happens the best thing to do is tolerate each other, respect each other, respect each other, and support each other